Tolerable Levels of Nonclinical Vehicles and Formulations Used in Studies by Multiple Routes in Multiple Species With Notes on Methods to Improve Utility - Gad, Shayne Cox; Spainhour, Charles B; Shoemake, Catherine; Pallman, Danielle R Stackhouse; Stricker-Krongrad, Alain; Downing, Philip A; Seals, Richard E; Eagle, Leslie Anne; Polhamus, Kara; Daly, Jennifer (International journal of toxicology, 2016)
Formulation of nonclinical evaluations is a challenge, with the fundamental need to achieve multiples of the clinical exposure complicated by differences in species and routes of administration-specific tolerances, depending on concentrations, volumes, dosing regimen, duration of each administration, and study duration. Current practice to approach these differences is based on individual experience and scattered literature with no comprehensive data source (the most notable exception being our 2006 publication on this same subject). Lack of formulation tolerance data results in excessive animal use, unplanned delays in the evaluation and development of drugs, and vehicle-dependent results. A consulting firm, a chemical company, and 4 contract research organizations conducted a rigorous data mining operation of vehicle data from studies dating from 1991 to 2015, enhancing the data from this author's 2006 publication (3 of the six 2015 contributors were also 2006 contributors). Additional data were found in the published literature. The results identified 108 single-component vehicles (and 305 combination formulations) used in more than 1,040 studies across multiple species (dog, primate, rat, mouse, rabbit, guinea pig, minipig, pig, chick embryo, and cat) by multiple routes for a wide range of study durations. The tabulated data include maximum tolerated use levels by species, route, duration of study, dose-limiting toxicity where reported, review of the available literature on each vehicle, guidance on syringe selection, volume and pH limits by route with basic guidance on nonclinical formulation development, and guidance on factors to be considered in nonclinical route selection.